Jalons pour une analyse comparée des concepts de mixité et d’hybridité - Susan (Trouvé) Finding; Vincent Latour (Cahiers du MIMMOC)
The terms ‘mixité’ (no direct translation is satisfactory) and hybridity may appear to be synonymous. How did these terms come to be at the centre of social issues in contemporary societies ? The questions raised around these issues are situated within the sphere of research on the theme of identity. The articles to be found in this volume examine the meanings given to the two terms as applied in sociology and politics in France, Britain and Spain. The analyses of the connotations given to ‘mixité’ and hybridity in the realms of social policy, community action, education and politics, serve to illustrate the differences and similitudes in approaches to integration in contemporary societies. The issue is of importance to French researchers, in particular to those working on Britain. The British model of integration, subject of recent publications in France, is used to cast a contrasting light on French practice.